2017
DOI: 10.1080/1369183x.2017.1388160
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity as skill: immigrant employment hierarchies in Norwegian low-wage labour markets

Abstract: Immigrants are often concentrated in particular, often low-waged, segments of the labour market and employers tend to assume that immigrants posit (soft) skills which make them particularly suited for specific tasks. Less scholarly attention has been given to the real and perceived content of these skills and how employers may shift their view over time. We contribute to the literature by examining changing ethnic employment hierarchies in two immigrant-intensive labour markets in Norway. Drawing on qualitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
97
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(129 citation statements)
references
References 28 publications
2
97
0
7
Order By: Relevance
“…Bertrand and Mullainathan, ; Hou and Coulombe, ), there is clear evidence that increased ethnic diversity in Europe was accompanied by stratification from the native‐born (Heath et al., ). Discrimination against visible minorities is prevalent across Europe regardless of the host‐country's migration history and political/economic policy (Heath and Cheung, ; Nordin and Rooth, ; Friberg and Midtbøen, ). In France, ethnic minorities experience persistent discrimination in the labour market (Ware, ) and those identified as black experience hiring discrimination (Riach and Rich, ) and are underrepresented in jobs involving customer contact (Combes et al., ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bertrand and Mullainathan, ; Hou and Coulombe, ), there is clear evidence that increased ethnic diversity in Europe was accompanied by stratification from the native‐born (Heath et al., ). Discrimination against visible minorities is prevalent across Europe regardless of the host‐country's migration history and political/economic policy (Heath and Cheung, ; Nordin and Rooth, ; Friberg and Midtbøen, ). In France, ethnic minorities experience persistent discrimination in the labour market (Ware, ) and those identified as black experience hiring discrimination (Riach and Rich, ) and are underrepresented in jobs involving customer contact (Combes et al., ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The employers described having the right soft skills as essential for considerations of suitability, while technical skills can be learned through internal training schemes. Previous research has similarly demonstrated how soft skills are central in employer demands in low-skilled work (Friberg & Midtbøen, 2018a;Moss & Tilly, 2003). Moss and Tilly (2003, p. 44) group soft skills into two clusters, interaction and motivation, where interactional skills include friendliness, teamwork, ability to fit in, and appropriate affect, grooming and attire, and motivational skills include enthusiasm, positive work attitude, commitment, dependability and willingness to learn.…”
Section: An Immigrant Job: Soft Skills and Devaluationmentioning
confidence: 90%
“…We further argue that this sense of place dissatisfaction or withdrawal from Dutch society among educated migrants is likely to be because of the education–occupation mismatch (Villarreal, ). Compared with low‐educated migrants, it is expected that educated migrants benefit less from migration because of their economic disadvantage and lack of opportunities in the fields of their educational qualification, often a result of racial and sociodemographic backgrounds (e.g., Djamba & Kimuna, ) and employment hierarchies associated with ethnicity (Friberg & Midtboen, ), among other reasons. This particular finding corroborates several other studies examining the link between PA and education (e.g., Lewicka, ; Maliepaard, Lubbers, & Gijsberts, ) and is well documented in the education–occupation mismatch literature (e.g., Hartog, ; Quintini, ; Villarreal, ).…”
Section: Discussionmentioning
confidence: 99%